Professional Resources - Papademas, Diane (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In support of visual sociology and teaching with film, video, photography, and visual media, a selection of professional resources follows. Professional associations journals, graduate study , and websites ahve been identified through the professional and scholarly networks of people, who may or may not identify with the visual sociology rubric. The resources suppor the intellectual movement of this field, and instructors and studetns may benefit from their use. Whenever possible changes ahve been edited into the material this eyar, and we expect that some addresses will have been altered in the interim.